Physico-Chemical and Biochemical Properties of Oil Extracted from Pistacia lentiscus - MIZI*, ABDELKADER; DJEDAIA, SALAH (Asian Journal of Chemistry, 2009)
A physico-chemical study and biochemical properties of the oil extractedfrom Pistacia lentiscus is presented. This shrub of Mediterraneanthe maquis type is established in the area El Kala. The extractedoil was carried out by two modes of extraction, the parameters of the fatcontent are given. According to the results this oil is comparable withthe olive-tree, it is composed by unsaturated fatty acids and a rather lowcontent of vitamin E of the order 6.6 mg/100 g.